Ligation of the Intersphincteric Fistula Tract (LIFT) Technique in the Treatment of Complex Perianal Fistula: Experience of First 50 Cases (Faridpur Medical College Journal, 2020)
Perianal fistula is a common disease and surgery is the only treatment option. Many surgical techniques have been described. Ligation of intersphincteric fistula tract (LIFT) is a sphincter saving surgical technique in which fistula tract is ligated and excised through intersphincteric approach. The aim of study is to present our experience of first 50 LIFT procedures particularly healing rate, recurrence rate and complications from the procedure. This is a prospective observational study started from March 2018 on whom underwent LIFT procedure for primary complex perianal fistula of infective origin at Faridpur Central Hospital and Faridpur Medical College Hospital. In this study, 50 patients (42 male and 8 female) of average age of 39±7.6 years with complex fistula were included. The mean operative time was 34.7±5.67 minutes and most of the fistulas were transsphincteric variety (90%). Median wound healing time was 21.45±6.34 days for intersphincteric wound and 26.78±6.93 days for the external opening of the fistula. Mean follow up period was 10.5 months. Seven patients of our series developed recurrent fistula, making the overall success of 86%. None of the patient in our series developed incontinence. LIFT procedure has the advantage of preservation of anal sphincter, minimal tissue injury, shorter healing time, relatively easy to perform, and high success rate. It's a good choice for treatment of complex perianal fistula.Faridpur Med. Coll. J. Jan 2020;15(1): 3-7